Financial burdens of Pregnancy: Understanding Socioeconomic, Demographic correlates and Out-of-pocket costs - Arumugam M.; Noorulla K.M.; Yasir M.; Kalwaniya M.; Siva H. (My University, 2025)
Introduction: In India, the financial burdens of pregnancy are closely tied to socioeconomic, and demographic factors, healthcare policies, and out-of-pocket costs. Health expenditure in India is around 3.2% of GDP, with public health spending making up less than half of the total expenditure. Several socioeconomic, and demographic factors significantly impact the financial burdens of pregnancy, particularly for women in vulnerable groups. Income, education, and geographical location strongly influence these costs. This study aims to investigate the socioeconomic, and demographic determinants of out-of-pocket expenditures (OOPE) during pregnancy and childbirth in the Agra district, Uttar Pradesh, India. Methods: The study utilized a cross-sectional mixed-methods design and collected data from participants through surveys and semi-structured interviews, involving different delivery locations among a diverse group of women who have given birth. The analysis focused on participants' socioeconomic, and demographic characteristics, direct and indirect expenditures, with contributing factors for OOPE and suggestions for reducing OOPE. Results: The study revealed impactful correlations between socioeconomic, and demographic factors and out-of-pocket costs during pregnancy, highlighting varying healthcare utilization patterns across delivery settings. Participants from diverse backgrounds experienced financial burdens in maternity-related care, with home deliveries showing minimal expenses but poorer healthcare access. Key factors contributing to impaired service utilization and strategies for reducing financial burdens were identified, underscoring the importance of targeted policies to enhance maternal healthcare access and affordability. Conclusion: The study's comprehensive analysis of socioeconomic, and demographic factors and out-of-pocket costs during pregnancy and childbirth provides crucial insights into the financial burdens faced by expectant mothers across diverse backgrounds. These findings underscore the necessity of targeted interventions to alleviate financial strain and improve maternal and child health outcomes through equitable access to essential care. Despite potential limitations like self-reporting bias and regional constraints, this research contributes significantly to understanding the financial aspects of pregnancy and underscores the need for supportive policies to alleviate the financial burden on expectant families. © 2024, Research Journal of Pharmacy and Technology. All rights reserved.